Can hydrothermal pretreatment improve anaerobic digestion for biogas from lignocellulosic biomass?. (February 2018) - Wang, Dou; Shen, Fei; Yang, Gang; Zhang, Yanzong; Deng, Shihuai; Zhang, Jing; Zeng, Yongmei; Luo, Tao; Mei, Zili
Highlights: Rice straw was hydrothermally-pretreated for anaerobic digestion in whole slurry. Hydrothermal pretreatment at lower temperatures can improve digestion performances. Digestion of pretreated rice straw at higher temperatures was inhibited seriously. Digestion was mainly decided by derived soluble matters rather than deconstruction. Pretreating rice straw at higher temperature was not advised for biogas production. Abstract: Hydrothermally-pretreated rice straw (HPRS) from various pretreatment temperatures was anaerobically-digested in whole slurry. Results indicated promoting pretreatment temperature significantly deconstructed rice straw, and facilitated the conversion of insoluble fractions to soluble fractions. Although 306.6 mL/g TS biogas was maximally yielded in HPRS-90 and HPRS-180, respectively, via digestion in whole slurry, it was only 3% promotion compared to the unpretreated rice straw. HPRS-210 yielded 208.5 mL/g TS biogas, which was 30% reduction with longer lag period of 19.8 d, suggesting serious inhibitions happened. Through slightly increasing organic loading, more serious acidification and reduction on biogas yield, especially at higher pretreatment temperatures, indicated the soluble fractions controlled digestion performances. Pearson correlation analysis suggested negative relationship existed between methane yield and the soluble fractions including soluble carbohydrates, formic acid and furfural. Hydrothermal pretreatment, especially at higher temperature, did not improve anaerobic digestion, thereby, was not recommended, however, lower temperature can be considered potentially.